Addressing Social Determinants of Health Identified by Systematic Screening in a Medicaid Accountable Care Organization: A Qualitative Study - Julia Browne; Jessica L. Mccurley; Vicki Fung; Douglas E. Levy; Cheryl R. Clark; Anne N. Thorndike (SAGE Publishing, 2021)
Introduction/Objectives: Systematic screening for social determinants of health (SDOH), such as food and housing insecurity, is increasingly implemented in primary care, particularly in the context of Accountable Care Organizations (ACO). Despite the importance of developing effective systems for SDOH resource linkage, there is limited research examining these processes. The objective of the study was to explore facilitators and barriers to addressing SDOH identified by systematic screening in a healthcare system participating in a Medicaid ACO. Methods: This qualitative case study took place between January and March 2020. Semi-structured interviews were conducted with fifteen staff (8 community resource staff and 7 managers) from community health centers and hospitals affiliated with a large healthcare system. Interviews were transcribed, coded, and analyzed using the Framework Method. Results: Facilitators for addressing SDOH included maintaining updated resource lists, collaborating with community organizations, having leadership buy-in, and developing a trusting relationship with patients. Barriers to addressing SDOH included high caseloads, time constraints, inefficiencies in tracking, lack of community resources, and several specific patient characteristics. Further, resource staff expressed distress associated with having to communicate to patients that they were unable to address certain needs. Conclusions: Health system, community, and individual-level facilitators and barriers should be considered when developing programs for addressing SDOH. Specifically, the psychological burden on resource staff is an important and underappreciated factor that could impact patient care and lead to staff burnout.